Pelatihan Penyusunan Laporan Keuangan Guna Meningkatan Kualitas Laporan Keuangan BUMDES di Desa Lawela Selatan, Buton Selatan - Nining, Nining Asniar Ridzal; Wayan, I Wayan Sujana (Welfare : Jurnal Pengabdian Masyarakat, 2023)
The purpose of this community service activity is to be able to provide knowledge and understanding to BUMDes managers on how to improve the quality of financial reports or how to prepare quality financial reports for BUMDes so as to produce financial reports in accordance with accounting standards that apply to BUMDes financial reports. Materials regarding BUMDes accounting include basic accounting and preparation of financial reports for BUMDes business units, as well as simulation of preparation or compilation of financial reports based on business units (services, trade). Implementation of Community Service Activities, namely regarding Techniques for Improving the Quality of BUMDes Financial Reports, including Recording and Reporting Finances in accordance with Types or Business Units to Managers or Managers of BUMDes Activities in Lawela Selatan Village, has been carried out well, and as a result, there has been an increase in knowledge of recording and financial reports for BUMDes Managers or Administrators, including types of business, elements of financial reports, the accounting cycle, general journal, special journal, preparation of financial reports, and SAK.